2019
DOI: 10.1093/aob/mcz112
|View full text |Cite
|
Sign up to set email alerts
|

Identification of salicylic acid-independent responses in an Arabidopsis phosphatidylinositol 4-kinase beta double mutant

Abstract: Background and Aims We have recently shown that an Arabidopsis thaliana double mutant of type III phosphatidylinositol-4-kinases (PI4Ks), pi4kβ1β2, constitutively accumulated a high level of salicylic acid (SA). By crossing this pi4kβ1β2 double mutant with mutants impaired in SA synthesis (such as sid2 impaired in isochorismate synthase) or transduction, we demonstrated that the high SA level was responsible for the dwarfism phenotype of the double mutant. Here we aimed to distinguish between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…In terms of growth size, this could be clearly seen in the WT, sid2, pi4kβ1β2 and sid2pi4kβ1β2 subsets. This has been previously used to distinguish between SA-dependent and SA-independent effects of pi4kβ1β2 deficiency [17,25]. Interestingly, in Šašek et al (2014) [25], we showed that crossing of pi4kβ1β2 with sid2 led to a fully reverted phenotype when plants were grown in soil for 4 weeks.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…In terms of growth size, this could be clearly seen in the WT, sid2, pi4kβ1β2 and sid2pi4kβ1β2 subsets. This has been previously used to distinguish between SA-dependent and SA-independent effects of pi4kβ1β2 deficiency [17,25]. Interestingly, in Šašek et al (2014) [25], we showed that crossing of pi4kβ1β2 with sid2 led to a fully reverted phenotype when plants were grown in soil for 4 weeks.…”
Section: Discussionmentioning
confidence: 57%
“…A good example is the pi4kβ1β2 mutant with impaired vesicle trafficking, which is a ubiquitous process that affects almost everything in plant cells [22]. We studied the SA-(in) dependent effects in pi4kβ1β2, showing that resistance to adapted pathogens is strictly SA-dependent, but callose production is SA-independent [17]. By creating this type of collection, we wanted to be able to compare more mutants with modulated SA patterns under exactly the same experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This fits together with the fact that a PA increase follows the recognition of MAMPs and DAMPs, but also the application of salicylic acid (SA) (Kalachova et al , 2013; Cacas et al , 2017; Gully et al , 2019). At the same time, chemical disruption of actin also triggers SA accumulation and SA‐responsive genes (Matouskova et al , 2014; Kalachova et al , 2019; Leontovycova et al , 2019). An activated SA pathway by actin disruption could even lead to increased plant resistance to pathogens (Leontovycova et al , 2019) (Fig.…”
Section: Figmentioning
confidence: 99%